The effect of institutional CSR on brand advocacy during COVID-19: the moderated mediation effect of CSR expectancy and value-driven motivation - Kim, Taeyoung; Yang, Jing; Yim, Myungok Chris (The journal of product & brand management, 2023)
Purpose This research aims to understand consumer responses to corporate social responsibility (CSR) during an unprecedented public health crisis. Specifically, two studies were conducted to investigate how companies’ different CSR initiatives in the early stage of COVID-19 would influence consumers’ advocacy intention according to their focus (i.e. targets of institutional CSR). The first study examined the moderating role of individuals’ CSR expectancy on the effects of companies’ CSR initiatives on consumers’ brand advocacy intention. The second study further extends the findings of Study 1 by examining the mediating role of perceived brand motive. Design/methodology/approach Two between-subject online experiments were conducted to explore the impact of three types of institutional CSR initiatives (i.e. community, employee and consumer-centered CSRs) on brand advocacy. Study 1 (N = 380) examined the moderating role of CSR expectancy in influencing consumer responses to institutional CSR initiatives. Study 2 (N = 384) explored the underlying mechanism through examining the mediating role of a company’s value-driven motivation in the process. Findings Study 1 indicated that institutional CSR, regardless of type, was more effective in generating a more significant brand advocacy intention than a promotional message, measured as a baseline. The impact of different kinds of institutional CSR on consumers’ brand advocacy intentions was significantly moderated by their CSR-related expectations. Specifically, individuals with moderate to high CSR expectancy showed higher brand advocacy intentions in both consumer- and employee-centered CSR initiatives than the promotional message. In comparison, those with low CSR expectancy only showed higher brand advocacy intentions in the community-centered CSR initiative. In addition, as individuals’ CSR expectations rose, the mediation effect of the perceived value-driven motivation became stronger. Research limitations/implications The current study includes guiding principles to help companies effectively respond to COVID-19 as corporate citizens by demonstrating the importance of individuals’ CSR expectancy across three CSR initiatives. This study used real-life examples of how leading companies were stepping up CSR efforts and suggested an approach that aligns CSR behaviors with the urgent and fundamental human needs of COVID-19. Originality/value In line with the CSR goal of maximizing benefits for stakeholders, this study’s findings signal that situational changes determine CSR expectations and that companies must be highly susceptible to the changes in consumers’ expectations of CSR and their appraisal process of CSR motives to maximize its CSR value.